Zirconium ions integrated in 1-hydroxyethylidene-1, 1-diphosphonic acid (HEDP) as a metalorganic-like complex coating on biodegradable magnesium for corrosion control. (November 2018) - Pu, Shimin; Chen, Meiyun; Chen, Yingqi; Zhang, Wentai; Soliman, Hanaa; Qu, Ai; Liu, Qijun; Tang, Xin; Huang, Nan; Wan, Guojiang
Graphical abstract: Highlights: A metal-organic complex coating was constructed on Mg for corrosion control. Zr ions were integrated into organic HEDP coating by alternating dip coating. The complex coating showed enhanced quality of closely-packed and firmly-anchored. The coating endowed Mg with slower corrosion and suppressed in-vitro degradation. Effectual corrosion control stems from the nature and improved quality of coating. Abstract: In this study, a coating of ionic Zr integrated in 1-hydroxyethylidene-1, 1-diphosphonic acid (HEDP) metalorganic-like complexes was applied on Mg for corrosion control. HEDP was first immobilized on alkaline pretreated Mg followed by an alternating dip-coating process of Zr ions and HEDP to build a complex coating on Mg. This coating was demonstrated to be homogeneous, compact and with a metalorganic-like framework firmly anchored on Mg. This coating led to reduced corrosion current densities and remarkably suppressed long-term in vitro degradation of Mg in phosphate buffer saline (PBS). This complex coating showed promise for surface modification of Mg in biodegradable applications.